Sex and virtue : an introduction to sexual ethics - Grabowski, John S. (Washington, District of Columbia : Catholic University of America Press, 2003)
DESCRIPTIONThis book discusses the moral dimensions of human sexuality from a Roman Catholic perspective.
Clashing symbols : sex, conscience, and authority -- Covenant and sacrament -- Kingdom, discipleship, character -- Sex and chastity -- Male and female : equality, difference, dignity -- Covenant fidelity, fertility, and the gift of self -- Teaching sex : education, sexuality, character.
Includes bibliographical references (pages 169-184) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Catholic Church -- Doctrines; Église catholique -- Doctrines; Catholic Church; Sex -- Religious aspects -- Catholic Church; Sexual ethics; Sexualité -- Aspect religieux -- Église catholique; Morale sexuelle; RELIGION -- Ethics; RELIGION -- Christian Theology -- Ethics; Sex -- Religious aspects -- Catholic Church; Sexual ethics; Theology, Doctrinal